Pulmonary function test: A critical domain in oral submucous fibrosis patients - Vishal Mehrotra; Sheenam Sambyal; Gauri Mishra; Kriti Garg; Rahul Srivastava; Saman Ishrat (Wolters Kluwer Medknow Publications, 2022)
INTRODUCTION: The study aims to measure and compare pulmonary function tests (PFTs) in oral submucous fibrosis (OSMF) patients (smokers/nonsmokers) and normal individuals. MATERIALS AND METHODS: The study population included 150 participants that comprised 50 nonsmoker OSMF patients, 50 OSMF patients who smoke as well, and 50 patients with no deleterious habits. Spirometer was used to assess PFT. RESULTS: Results showed that a significant P value was obtained for forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), FEV1/FVC, peak expiratory flow rate (PEFR), and maximum voluntary ventilation (MVV) and also for the predicted values of FEV, FEV1, FEV1/FVC, PEFR, and MVV in OSMF (smokers/nonsmokers) study groups. CONCLUSION: Thus, the decrease in pulmonary function can be an alarming sign for restrictive type of pulmonary disease.